ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU PLAT BESI INDUSTRI KAROSERI MENGGUNAKAN METODE EOQ (Studi Kasus Pada PT. MISITAMA) - Paduloh Paduloh (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2018)
This study aims to analyze the optimal usage volume of iron raw plates required by PT. Misitama for the period of 2017. PT. Misitama is a company engaged in the field of tank manufacturing industry for the needs of manufacturing and mining industries. The study analyzed the total cost of Iron Iron raw material supply which must be used by PT. Misitama during 2017, analyzing reorder point, safety stock and raw material inventory control using EOQ method. The data used is the data of September 2017 - October 2017. The data used is secondary data derived from corporate data. The results show that the amount of raw material purchases during 2017 if using the EOQ method becomes lower. The optimal purchase of raw materials to be done by the company in 2017 is 14.8 m2 with the frequency of ordering to be done as much as 8 times. The quantity of safety stock (Safety Stock) that must be available in warehouse of 7 m2 and reorder point (reorder point) EOQ that is when the warehouse inventory is only 8.88 m2. Total inventory cost for production process issued by PT. Misitama by using EOQ method becomes smaller than the total cost of previous inventory.